Pengaruh Hydrotherapy dalam Asuhan Keperawatan Pasien dengan Nyeri Arthritis - Munarji, Rahmi Pratiwi; Chayati, Nur (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
Introduction – Arthritis is an inflammatory and painful process that occurs around the joints of the body. The cause of the disease can be due to several factors, namely trauma, burden on the joints, age, gender, history of disease, obesity, and excessive strenuous activity behaviour. This behaviour if it lasts a long time will cause pain and discomfort and can interfere with daily activities. So that efforts are needed to reduce the pain felt by patients through hydrotherapy. Purpose - To determine the effect of hydrotherapy on reducing pain in patients with arthritis. Methodology - patient arthritis. Activities carried out by conducting assessment, implementation, and evaluation of nursing. Finding – Mrs. S, a 41-year-old woman, was diagnosed arthritis with complaints of leg pain for more than 3 months. Mrs’s is not currently taking painkillers. The research activities are education and hydrotherapy using warm water (40oC) once a day for 15 minutes. After 3 days the pain in the legs decreased from a scale of 5 to 3. It can be concluded that hydrotherapy has been proven to be able to reduce the patient's joint pain. Originally/Value/Implication - This therapy can be applied to reduce pain and discomfort in the feet of arthritis, but the use of therapy can have a better impact if additional therapy time is added so as to increase the effectiveness of therapy